Deteksi pepsin pada penderita refluks laringofaring yang didiagnosis berdasarkan reflux symptom index dan reflux finding score - Andriani, Yunida; Akil, Muhammad Amsyar; Gaffar, Masyita; Punagi, Abdul Qadar (PERHATI-KL, 2011)
Background: It is estimated that more than 50% of patients with voice disorders who come fortreatment are caused by laryngopharyngeal reflux (LPR). LPR has been implicated in the etiology ofmany laryngeal disorders including subglottic stenosis, laryngeal carcinoma, laryngeal contact ulcer,laryngospasm and vocal nodule on the vocal cords. Ambulatory 24 hour double-probe (pharyngeal andesophageal) pH monitoring is the gold standard examination for diagnosing LPR, but it is still far fromideal criteria.The assessment of pepsin in airway secretions could be used as a sensitive diagnosticmarker of LPR because pepsin is not synthesized by any type of airway cells. Purpose: The aim ofthis study was to detect the presence of pepsin on laryingopharyngeal reflux patients which diagnosedbased on reflux symptom index (RSI) dan reflux finding score (RFS) at Wahidin Sudirohusodo Hospital,Makassar. Methods: This is a comparative quantitative study. We performed RSI and RFS examinationson 51 samples, followed by saliva pepsin detection using ELISA method on 48 samples, then analyzed withSpearman’s Rho test. Result: RSI score >13 was found in 48 samples (94,12%) and RFS score >7 wasin 51 samples (100%). Pepsin was detected on all sputum samples, however there was no significant relationship betwen RSI and RFS scoring with the level of pepsin in saliva (p>0.01). Conclusion: Pepsin was detected on saliva of patients with laringopharyngeal reflux who was diagnosed based on RSI andRFS. We concluded that RSI and RFS can be used as diagnostic tools for LPR. Keywords: laringopharyngeal reflux, reflux symptom index, reflux finding score, pepsin Abstrak : Latar belakang: Diperkirakan lebih dari 50% pasien dengan gangguan suara yang datang berobatke dokter THT diakibatkan oleh refluks laringofaring (RLF). Diduga RLF berperan pada patogenesissejumlah kelainan pada laring, termasuk stenosis subglotik, karsinoma laring, laryngeal contact ulcers,laringospasme dan vokal nodul pada pita suara. Pemeriksaan ambulatory 24 hour double-probe pHmonitoring merupakan gold standard untuk mendiagnosis RLF, namun pemeriksaan ini masih jauh darikriteria ideal. Menentukan adanya pepsin pada sekret saluran napas merupakan petanda diagnostik yangsensitif untuk RLF karena pepsin tidak dihasilkan oleh sel apapun dalam saluran napas. Tujuan: Penelitianini bertujuan mendeteksi keberadaan pepsin pada penderita refluks laringofaring yang didiagnosisberdasarkan refluks symptom index (RSI) dan reflux finding score (RFS). Metode: Jenis penelitian iniadalah komparatif kuantitatif. Dilakukan pemeriksaan RSI dan RFS pada 51 percontoh dan dilanjutkandengan pemeriksaan pepsin saliva menggunakan metode ELISA pada 48 percontoh lalu dilakukan ujiSpearman’s Rho. Hasil: Skor RSI >13 sebanyak 48 percontoh (94,12%) dan skor RFS >7 sebanyak 51percontoh (100%). Pepsin terdeteksi pada saliva semua percontoh. Tidak ada hubungan yang bermaknaantara skoring RSI dan RFS dengan kadar pepsin pada saliva (p>0,01). Kesimpulan: RSI dan RFS dapatdigunakan dalam menegakkan diagnosis RLF. Kata kunci: refluks laringofaring, reflux symptom index, reflux finding score, pepsin